Diversity of Sea Shore Invertebrates at West Coast Peninsular Malaysia - Nur Izzah Farzana Mohd Rafi; Irdeena Maisarah, Ishak; Rahayu Ahmad; Mohd Sanusi,Mohamed; Mohamad Arif Iskandar Abdul Wahab; Faszly Rahim; Ehwan Ngadi (Universiti Sains Islam Malaysia, 2024)
Junior Researcher International Conference (iJURECON) Kolej Genius Insan (KGI) 17 dan 18 November 2020 Pages : 42-47